The efficiency of online cognitive-behavioral therapy for postpartum depressive symptomatology: a systematic review and meta-analysis. Issue 1 (2nd January 2020) - Roman, Maria; Constantin, Ticu; Bostan, Cristina Maria
ABSTRACT: Postpartum depression (PD) is a frequently occurring disorder that affects the cognitive, emotional and social development of a mother after childbirth. Online cognitive-behavioral therapy (OCBT) is used as therapy for PD symptomatology, but no clear evidence is available about its effectiveness. The goal of this meta-analysis was to identify, synthesize and analyze the empiric studies regarding the OCBT effectiveness for PD. A search for indexed articles and unpublished theses between 2000 and 2017 was made in Google Scholar, Proquest, ScienceDirect, APA PsycNet, Cochrane, SpringerLink, Medline, PubMed and Dissertations Abstract International. Six studies were selected based on the following eligibility criteria: (1) papers published in English, (2) papers about PD, (3) papers that empirically investigated the effectiveness of OCBT for PD, and (4) papers comparing an experimental group with a control group. Exclusion criteria included investigations of PD for: (1) mothers diagnosed with another severe disorder and (2) mothers with deceased children and (3) women with an age below 18 years old. This meta-analytic study identified a moderate significant size-effect ( d = – 0.54, 95% CI [−0.716; −0.423]) of the OCBTs in reducing PD, and practical implications and limitations are discussed.